2020
DOI: 10.1007/s00415-020-10321-8
|View full text |Cite
|
Sign up to set email alerts
|

Mononeuritis multiplex: an unexpectedly frequent feature of severe COVID-19

Abstract: The prolonged mechanical ventilation that is often required by patients with severe COVID-19 is expected to result in significant intensive care unit-acquired weakness (ICUAW) in many of the survivors. However, in our post-COVID-19 follow-up clinic we have found that, as well as the anticipated global weakness related to loss of muscle mass, a significant proportion of these patients also have disabling focal neurological deficits relating to multiple axonal mononeuropathies. Amongst the 69 patients with sever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 12 publications
0
65
1
6
Order By: Relevance
“…Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 220 patients with Guillain-Barré syndrome (GBS) 4 and 41 patients with non-GBS neuropathy were retrieved 5,6,7,8,9,10,11,12,13,14 . The age of these 261 patients, reported in 244 of them, ranged from 8 to 94 years.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 220 patients with Guillain-Barré syndrome (GBS) 4 and 41 patients with non-GBS neuropathy were retrieved 5,6,7,8,9,10,11,12,13,14 . The age of these 261 patients, reported in 244 of them, ranged from 8 to 94 years.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found in several post-COVID-19 follow-up cases that together with a global weakness related to loss of muscle mass, 16% of patients present with disabling focal neurological deficits relating to multiple axonal mononeuropathies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, neuroimaging studies have commonly described cerebral microhaemorrhages occurring in those with severe COVID-19, reminiscent of microangiopathic disorders such as amyloid and hypertensive angiopathies [100,104,105], a phenomenon borne out in pathology series [32,75,100,106]. As would be expected in a disorder of the endothelium, similar microvascular changes have been described in multiple organ systems [107], and it has even been suggested that this process might be the cause of the mononeuritis multiplex seen in a substantial minority of survivors of severe COVID-19 [108].…”
Section: Neurovascular and Thromboembolic Diseasementioning
confidence: 91%